Recovery of benthic macroinfauna six years after dredging - David Samuel Johnson; Manisha Pant; Andrew Nemeth; Emelie Foster; Adam Gartelman; Stacy Calhoun-Grosch; Kehui Xu; Brian J. Roberts; James Nelson (PLoS ONE, 2025)
In soft-sediment communities, benthic macroinfauna can recover quickly (sometimes < 1 year) from dredging. However, it’s unclear how recovery is influenced if dredging dramatically changes abiotic factors. We determined recovery of benthic macroinfauna from dredging on a sandy shoal (Ship Shoal, Louisiana, USA), six years after dredging. Because the dredged area infilled with mud instead of sand and changed local abiotic conditions, we hypothesized that the benthic community had not recovered. Our results support this hypothesis. Although the dredged community had, on average, 160% greater density and 170% greater macroinfaunal biomass than the reference community, these increases were driven by the opportunistic and seasonally variable dwarf clam, Mulinia lateralis. Community structure differed starkly between the regions. Haustoriid amphipods and amphioxus (Branchiostoma floridae) dominated the reference community. However, these taxa were largely absent from the dredged community, which was dominated by opportunistic species such as M. lateralis and the fringe-gilled mudworm Paraprionospio pinnata. Community differences were largely driven by bottom-water dissolved oxygen and sediment grain size. Our results suggest that the dredged areas are still in a transitional phase of recovery after six years – dominated by opportunistic, hypoxia-tolerant species. Our results suggest that abiotic factors such as grain size and hypoxia are important in structuring benthic communities and their recovery rates. Thus, to achieve faster recovery of the biological community, dredging should be conducted in a way that minimizes long-term impacts on abiotic conditions.